P01.013 Long-term analyses of the NOA-08 randomized phase III trial of temozolomide versus radiotherapy for elderly patients with malignant astrocytomas. (19th September 2018) - Wick, A; Kessler, T; Platten, M; Meisner, C; Bamberg, M; Herrlinger, U; Felsberg, J; Weyerbrock, A; Seidel, C; Steinbach, J P; Sabel, M; Vesper, J; et al.
Abstract: Background: While the NOA-08 trial and the NORDIC Elderly trial suggested an O6-methylguanine DNA-methyl transferase (MGMT) status-tailored use of radiotherapy (RT) and temozolomide (TMZ), recent data from the NCIC CE.6/EORTC 26062 showed that hypofractionated RT plus TMZ was superior to RT for unselected elderly patients with an impact of MGMT for the effect of TMZ. Material and Methods: This is the long-term update of the NOA-08 trial (German Cancer Trials Registry ID 386 and NCT01502241) that compared efficacy and safety of RT alone to TMZ alone in elderly patients with anaplastic astrocytoma (AA) or glioblastoma (GB), both isocitrate dehydrogenase wildtype, using overall survival (OS) as primary endpoint and event-free survival (EFS) as well as efficacy according to MGMT status as major secondary endpoints. NOA-08 had randomized patients (N=412; 39 AA, 373 GB) > 65 years with a Karnofsky performance score ≥ 60 in electronically generated blocks of variable length without stratification to receive standard RT to 60 Gy in 30 x 2 Gy fractions or TMZ dosed according to tolerance in a one week on/one week off schedule with tolerability dependent dosing. The trial finished enrolment Nov 2 2009 and demonstrated non-inferiority of TMZ compared with RT (p=0·033). Results: In the long-term analysis with a data cut-off Apr 1 2018 median OS was 8·2 [7·0–10·0] months for TMZ treatment versus 9·4 [8·1–10·4] months for RT; hazard ratio (HR)=0·93 (95% CI: 0·76-1·15)] of TMZ versus RT did not differ between both arms. Also, median EFS [3·4 [3·2–4·1] months versus 4·6 [4·2–5·0] months did not differ with a HR=1·02 (0·83-1·25)]. MGMT promoter methylation tested in tumor tissue (82/221 patients, 37·1%) was associated with prolonged OS [13·6 [10·1–16·5] versus 8·0 [6·9-9·9] months; HR=0·53 (0·40-0·70), p<0·0001]. Patients with MGMT promoter methylation had longer OS and EFS when treated with TMZ (18·4 [13·9–24·4] months and 8·5 [6·9–13·3] months) versus RT (9·6 [6·4–13·7] months and 4·8 [4·3–6·2] months, HR 0·44 [0.27–0.70], p<0·001 for OS and 0·46 [0.29–0.73], p=0·001 for EFS). Patients without MGMT promoter methylation had shorter EFS and a shorter OS with the usual testing not significant when treated with TMZ (6·7 [5·6–8·2] months and 3·0 [2·6-3·3] months) versus with RT (10·2 [8·0–12·0] months and 4·6 [3·7-6·4] months), HR 1·33 [0·95-1·87], p=0·099 for OS and 1·86 [1·32-2·62], p<0·001 for EFS). Conclusion: Also in the long-term analyses, NOA-08 confirms the non-inferiority of TMZ compared with RT in the treatment of elderly patients with WHO grade III or IV astrocytic gliomas. To improve OS and EFS, MGMT promoter methylation is a strong predictive biomarker for the choice between RT and TMZ and offers unexpectedly favorable long-term outcome with initial TMZ monotherapy.